Enthalpy and Heat Transfer Simulation of Reline Based Nanofluid Flowing in an Elliptic Shaped Duct - Puneeth, V.; Narayan, Shankar S; Aly, Emad H; Anwar, M. Shoaib (Journal of Applied Nonlinear Dynamics, 2026)
Reline, being a sub–class of ionic liquids consisting of hydrogen bond acceptor (HBA) and hydrogen bond donor (HBD), exhibits properties such as low melting points, high thermal stability, and tunable properties. It is one of the deep eutectic solvents with the composition Choline Chloride–Urea and is also known as an environmentally friendly solvent in various chemical processes. This attribute of the reline aligns well with sustainable practices in the chemical industry as an impressive alternative to conventional solvents. Its application extends to some of the major fields that mankind is dependent upon, such as pharmaceuticals, biotechnology, energy storage, etc. On the other hand, single–walled carbon nanotubes provide a higher thermal conductivity and specific heat capacity, making them useful in various heat exchangers, thermal storage systems, metallurgical applications, etc. Hence, in this study, the nanofluid is formed by considering reline as the base fluid with SWCNT suspensions. The simulation is performed to understand the various aspects of reline–based nanofluid flow inside elliptic ducts. The study explores the impact of the Reynolds number, the aspect ratio of the duct, and the thermophysical properties of SWCNT-reline nanofluid on the system’s behaviour. Navier–Stokes’ equation is utilised to perform the Mathematical analysis to understand the flow and heat transfer behaviour of SWCNT-reline nanofluid. From the results, it was clearly observed that the velocity at the narrow region decreased as the pressure rose, and Reynold’s number profile indicated the presence of turbulent flow behaviour.